2021
DOI: 10.1038/s41467-021-24914-y
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal-derived FGF15 protects against deleterious effects of vertical sleeve gastrectomy in mice

Abstract: Bariatric surgeries such as the Vertical Sleeve Gastrectomy (VSG) are invasive but provide the most effective improvements in obesity and Type 2 diabetes. We hypothesized a potential role for the gut hormone Fibroblast-Growth Factor 15/19 which is increased after VSG and pharmacologically can improve energy homeostasis and glucose handling. We generated intestinal-specific FGF15 knockout (FGF15INT-KO) mice which were maintained on high-fat diet. FGF15INT-KO mice lost more weight after VSG as a result of increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 116 publications
1
18
0
Order By: Relevance
“…Notable in mice that received SG was an expansion of Lactobacillus subspecies. We and others have consistently observed that SG led to considerable increases in the richness of Lactobacillus in obese rodents ( 22 , 23 , 43 ). These microbes are generally regarded as “healthy” bacteria and can be found in a variety of foods and probiotics which are often used to treat intestinal health issues ( 44 , 45 ).…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…Notable in mice that received SG was an expansion of Lactobacillus subspecies. We and others have consistently observed that SG led to considerable increases in the richness of Lactobacillus in obese rodents ( 22 , 23 , 43 ). These microbes are generally regarded as “healthy” bacteria and can be found in a variety of foods and probiotics which are often used to treat intestinal health issues ( 44 , 45 ).…”
Section: Discussionsupporting
confidence: 60%
“…Bariatric surgery has been reported to change the gut microbial populations ( 22 , 23 ), and alterations in the gut microbiota have been pointed as a potential modulator of the colonic inflammation observed in obesity ( 40 ). Therefore, we next characterized the intestinal bacterial changes following SG.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bozadjieva-Kramer et al (2021) performed vertical gastrectomy-induced osteopenia studies in intestinalspecific FGF15 null mice, revealing that intestinal FGF15 has positive effects on skeletal metabolism (30). The authors postulated that intestinal FGF15 protects against bone loss by restricting serum bile acid levels, but the role of the intestinal FXR-FGF15 axis and serum bile acids were not investigated (30). Appreciating that the FXR-FGF15 axis regulates endogenous intestinal FGF15 production, work by Bozadjieva-Kramer et al (2021) supports the concept that the intestinal FXR-FGF15 axis is a candidate regulator of bone metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…Bozadjieva-Kramer et al performed vertical gastrectomy-induced osteopenia studies in intestinal specific FGF15-null mice, revealing that intestinal FGF15 has positive effects on skeletal metabolism ( 30 ). The authors postulated that intestinal FGF15 protects against bone loss by restricting serum bile acid levels, but the role of the intestinal FXR/FGF15 axis and serum bile acids were not investigated ( 30 ).…”
Section: Introductionmentioning
confidence: 99%